2011
DOI: 10.1001/jama.2010.1983
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Vaccine in Older Adults and the Risk of Subsequent Herpes Zoster Disease

Abstract: Context Approximately 1 million episodes of herpes zoster occur annually in the United States. Although prelicensure data provided evidence that herpes zoster vaccine works in a select study population under idealized circumstances, the vaccine needs to be evaluated in field conditions. Objective To evaluate risk of herpes zoster after receipt of herpes zoster vaccine among individuals in general practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(157 citation statements)
references
References 33 publications
8
142
0
7
Order By: Relevance
“…Studies revealed that 2 doses of HZ/su containing 50 μg of recombinant VZV glycoprotein E administered at 1-or 2-month intervals were well-tolerated and induced much more robust VZV-specific and VZV glycoprotein E-specific CD4 + T cell and antibody responses than did vOka (55,56). A randomized placebo-controlled study of 15,411 subjects ≥ 50 years of age revealed a remarkable 97.2% efficacy in preventing zoster for a 3.2-year period that did not diminish with increasing age (57).…”
Section: Gsk Vaccine (Hz/su)mentioning
confidence: 99%
“…Studies revealed that 2 doses of HZ/su containing 50 μg of recombinant VZV glycoprotein E administered at 1-or 2-month intervals were well-tolerated and induced much more robust VZV-specific and VZV glycoprotein E-specific CD4 + T cell and antibody responses than did vOka (55,56). A randomized placebo-controlled study of 15,411 subjects ≥ 50 years of age revealed a remarkable 97.2% efficacy in preventing zoster for a 3.2-year period that did not diminish with increasing age (57).…”
Section: Gsk Vaccine (Hz/su)mentioning
confidence: 99%
“…14 To date, only 2 estimates of HZ vaccine effectiveness have been published. 15,16 Both studies used electronic-billing data without medical record confirmation which can result in misclassification of both exposure (vaccination status) and outcome (occurrence of HZ). 1,17 Furthermore, neither provided clinical information on HZ characteristics among vaccinated persons, precluding a complete description of the vaccine's impact.…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study, using routinely collected claims data from the Kaiser Permanente health plan in the USA, identified 75,761 vaccinated individuals over 60 years and matched each to three unvaccinated controls; the incidence of zoster was reduced by 55% in those vaccinated [85]. Unpublished data from the Clinical Practice Research Datalink, a routinely collected primary care database of almost 13 million patients in the UK, suggests that among patients in England aged between 65 and 84 years, there has been a 22% decline in consultations for zoster among those eligible for vaccination, compared to those ineligible [66].…”
Section: Development Of a Vaccine Against Zoster Efficacy And Safetymentioning
confidence: 99%